The newspaper in ethics class (Journal of Parents and Teachers, 2026)
The use of newspapers in ethics classes gives students access to news stories that are relevant to ethical learning. This approach encourages reflection, critical analysis, participation and an appreciation of diversity, responsibility and sustainability.
Keywords: Ethics, News, Analysis, Reflection, and Education.